Pengembangan Modul Mata Kuliah Bahasa Indonesia dI Stimik Stikom Indonesia Berbasis Proyek - Ni Kadek Nita Noviani Pande; Ida Bagus Putrayasa; I Made Sutama (Universitas Muhammadiyah Makassar, 2020)
This research is a development research that aims to (1) describe the project-based Indonesian Language module, (2) describe the responses of content experts, module design experts, lecturers, students, and (3) describe the effectiveness of the module seen from student learning outcomes. The test subjects in this study were STMIK STIKOM Indonesia students. Data collection method used is questionnaire. Data were analyzed using qualitative descriptive and quantitative descriptive techniques. The results of the study are 1) project-based Indonesian language print modules, 2) the content expert's response states that the module is well qualified with a percentage level of 88.33% then module design experts obtain a percentage of 77.5%, the course lecturer states that the module is good to use obtained a percentage of 84.44% while the test responses of 3 students, 10 students and 30 students showed that the modules obtained percentages of 93.33%, 83.6%, and 82.93%, and 3) the effectiveness of project-based subject modules seen from the results Student learning is a significant difference between the average score of student learning outcomes before using project-based modules and after using project-based modules.